Baseline white matter hyperintensities affect the course of cognitive function after small vessel disease‐related stroke: a prospective observational study. (12th November 2020) - Fruhwirth, V.; Enzinger, C.; Fandler‐Höfler, S.; Kneihsl, M.; Eppinger, S.; Ropele, S.; Schmidt, R.; Gattringer, T.; Pinter, D.
Abstract : Background and purpose: Cognitive impairment is a common sequel of recent small subcortical infarction (RSSI) and might be negatively affected by preexisting cerebral small vessel disease (SVD). We investigated whether the course of cognitive function in patients with RSSI is influenced by the severity of white matter hyperintensities (WMH), an important imaging feature of SVD. Methods: Patients with magnetic resonance imaging (MRI)‐proven single RSSI were tested neuropsychologically concerning global cognition, processing speed, attention, and set‐shifting. Deep and periventricular WMH severity was assessed using the Fazekas scale, and total WMH lesion volume was calculated from T1‐weighted MRI images. We compared baseline function and course of cognition 15 months after the acute event in patients with absent, mild, and moderate‐to‐severe WMH. Results: The study cohort comprised 82 RSSI patients (mean age: 61 ± 10 years, 23% female). At baseline, 40% had cognitive impairment (1.5 standard deviations below standardized mean), and deficits persisted in one‐third of the sample after 15 months. After age correction, there were no significant differences in set‐shifting between WMH groups at baseline. However, although patients without WMH (deep: p < 0.001, periventricular: p = 0.067) or only mild WMH (deep: p = 0.098, periventricular: p = 0.001) improved in set‐shifting after 15 months, there was no improvement in patients with moderate‐to‐severe WMH (deep: p = 0.980, periventricular: p = 0.816). Baseline total WMH volume ( p = 0.002) was the only significant predictor for attention 15 months poststroke. Conclusions: This longitudinal study demonstrates that preexisting moderate‐to‐severe WMH negatively affect the restoration of cognitive function after RSSI, suggesting limited functional reserve in patients with preexisting SVD. Abstract : Preexisting moderate‐to‐severe white matter hyperintensities negatively affect the restoration of cognitive function after recent small subcortical infarct, suggesting limited functional reserve in patients with preexisting small vessel disease.